"A Child in Every Artist?" Vjera Biller and Jewish Primitivism in the Berlin Sturm Avant-garde. Issue 1 (1st January 2021) - Wilhelm, Mirjam E.
Abstract : This article centers on the "forgotten" Jewish avant-garde artist Vjera Biller, among the most active contributors to the Berlin-based 1920s expressionist movement Der Sturm . Through an in-depth analysis of the artist's fragmented oeuvre, including her Venice series, it examines Biller's art practice, her leitmotif of children, and its links to the aesthetics of interwar German Expressionism. It contrasts her approach with that of her contemporary Sturm colleague Marc Chagall and shows how both artists drew extensively on children's art and "the primitive" for inspiration. Biller also pioneered the inclusion of popular culture elements such as cartoons and comics as an avant-garde art form.